To solve the system of equations using the substitution method, we start with the two given equations:
- \( x = y - 4 \)
- \( x + 8y = 2 \)
We will substitute the expression for \( x \) from the first equation into the second equation.
Substituting \( x = y - 4 \) into \( x + 8y = 2 \):
\[ (y - 4) + 8y = 2 \]
Now, simplify the equation:
\[ y - 4 + 8y = 2 \]
Combine like terms:
\[ 9y - 4 = 2 \]
Next, add 4 to both sides:
\[ 9y = 6 \]
Now, divide both sides by 9:
\[ y = \frac{6}{9} = \frac{2}{3} \]
Now that we have the value for \( y \), we substitute it back into the first equation to find \( x \):
\[ x = y - 4 = \frac{2}{3} - 4 \]
To perform the subtraction, convert 4 into a fraction:
\[ x = \frac{2}{3} - \frac{12}{3} = \frac{2 - 12}{3} = \frac{-10}{3} \]
Thus, the solution to the system of equations is:
\[ \left( \frac{-10}{3}, \frac{2}{3} \right) \]
In decimal form, this corresponds to \( (-3.33, 0.67) \).
Looking at the options provided, it appears that none of the options exactly match this result. However, the closest matching format, if re-written, is:
\[ (-3 \frac{1}{3}, \frac{2}{3}) = \left( -\frac{10}{3}, \frac{2}{3} \right) \]
So, the answer choice that matches this solution is:
\[ \left( -3 \frac{1}{3}, \frac{2}{3} \right) \]